PENGARUH TAYANGAN STAND UP COMEDY INDONESIA SEASON 7 DI KOMPAS TV TERHADAP PERSEPSI KOMIKA KOMUNITAS STAND UP INDO PKU - Dani Abdillah; Evawani Elysa Lubis Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Various programs are presented by television stations. They are competing to be able to present interesting and interesting programs for many people. One of is The program of Stand Up Comedy Indonesia Season 7 in Kompas TV tells us that competition comedy is in different style from the others. This comedy program also has the tagline